Opportunity for using WLAN with IEC 61850 and the future of this protocol - Ali, Nasser Hasan; Mohd Ali, Borhanuddin; Basir, Otman; Othman, Mohammad Lutfi; Hashim, Fazirulhisyam; Aker, E. (Universiti Putra Malaysia Press, 2017)
The unified protocols are unified in application interface, models, and seamless. They generate one standard protocol, one world called IEC 61850. IEC 61850 integrate the security, interoperability, modelling, mapping to a substation, and reliability. Presently, the more expensive fiber based Ethernet LAN is the most prevalent technology for medium and low voltage distribution substations. To circumvent this problem Wireless Local Area Network (WLAN) has been investigated for its suitability for applications that are compliant to IEC 61850: automation and metering; control and monitoring; and over-current protection. In this paper the IEEE 802.11n WLAN is studied when used in various IEC 61850 supported applications for substation automation. It also discusses the benefits of using GOOSE message to protect and control applications and the use of IEC 61850.